Analisis Didaktik Calon Katekisasi Sidi Untuk Pendewasaan Iman Warga Gereja di Jemaat Gmim Sion Picuan Minahasa Selatan - Eremtrouw Pattinasarany; Semuel Selanno; Wolter Weol (Jurnal Ilmiah Wahana Pendidikan, 2021)
One of the services carried out by the Christian Church in Indonesia (GMIM) is Catechization (Sidi). In order to become a man who has more faith in Christ, he needs to be educated and educate himself. "Humans can be human only through education". So this action that is taken by the church in shaping the maturity of the congregation's faith is carried out through sidi catechism. Because catechism is a form of Christian education service carried out by the church. So the purpose of this study is to analyze and describe: How is the didactic form of sidi catechism for church members in the GMIM congregation. This research is a qualitative research with the type of library research. Based on the results of the research, the authors conclude that this Sidi Catechism education has a significant role as an introduction for followers to reach maturity in religion and society, especially for church members with some guidelines in the form of a curriculum that has been provided. Because this catechetical education has been a mainstay throughout history in the regeneration of Christianity